2015
DOI: 10.1088/0957-4484/26/22/225301
|View full text |Cite
|
Sign up to set email alerts
|

Parallel nanomanufacturing via electrohydrodynamic jetting from microfabricated externally-fed emitter arrays

Abstract: We report the design, fabrication, and characterization of planar arrays of externally-fed silicon electrospinning emitters for high-throughput generation of polymer nanofibers. Arrays with as many as 225 emitters and with emitter density as large as 100 emitters cm(-2) were characterized using a solution of dissolved PEO in water and ethanol. Devices with emitter density as high as 25 emitters cm(-2) deposit uniform imprints comprising fibers with diameters on the order of a few hundred nanometers. Mass flux … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…8. Although several pieces of similar networks can be found in holey/lacey carbon or cellulose nanocrystal films after instable polymer/solvent evaporation 26,27 , large-scale fabrication of such nanofibrous networks has never before been reported 46,47 . Here, we can easily fabricate a PVDF nano-net membrane with an area of 55 × 70 cm 2 (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…8. Although several pieces of similar networks can be found in holey/lacey carbon or cellulose nanocrystal films after instable polymer/solvent evaporation 26,27 , large-scale fabrication of such nanofibrous networks has never before been reported 46,47 . Here, we can easily fabricate a PVDF nano-net membrane with an area of 55 × 70 cm 2 (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Different jet heads are used in the melt and the solution electrospinning: a nozzle (to provide wire or melt feeding) or a syringe (to provide solution flow). Different designs of the jet head are investigated aiming to provide efficient material feed, including composites [22,24]. Electrospun fibers have been investigated for different biomedical applications, such as drug delivery.…”
Section: Customization Of Electrospinning Devicementioning
confidence: 99%
“…The type of the collector used in the process has significant influence on the distribution of the fibers, and further on the porous scaffold sample. Different types of collectors can be used for electrospinning process and new designs have been investigated, especially in combination with multiple electrospinning sources [22,24]. High voltage brought to the collector (or the needle) creates a very strong electric field which elongates the droplet and creates fibers that are further attached to the collector.…”
Section: Customization Of Electrospinning Devicementioning
confidence: 99%
See 1 more Smart Citation
“…Microfabrication technology can circumvent some of the manufacturing challenges faced by these systems including the tight control of the dimensions, the monolithic creation of the emitter arrays with the feedstock supply network, and the miniaturization of the emitters to achieve larger emitter density and operation at less bias voltage. In particular, Ponce de Leon et al reported a planar electrospinning emitter array made of silicon via deep reactive-ion etching with 225 emitters spaced 2 mm [35].…”
Section: Introductionmentioning
confidence: 99%